Rastros visuais para experiências (im)possíveis: pedagogias para ver e narrar a cidade - Souza, Raquel Salazar Ribeiro e (Universidade Federal de São Carlos, 2025)
This thesis investigates the relationships between memory, experience, and creation based on educational practices of the Olhares (Im)possíveis collective, formed by young people from Ouro Preto since 2017. It analyzes how the images produced and the collective practices reconfigure ways of seeing and narrating the city. The research understands filmmaking as a space of encounter, listening, and invention, where new forms of inhabiting the urban are created. Inspired by Walter Benjamin, Jorge Larrosa, Georges Didi-Huberman, Jacques Rancière, Cezar Migliorin, Paola Berenstein Jacques, and Susan Sontag, it articulates concepts of experience, image, and montage. The study focuses on the productions of the collective between 2017 and 2023 (films, photographs, audio recordings, conversations, and workshops) understood as a living archive that fabulates and reinscribes the city’s memories. The central question guiding this investigation is: how do the audiovisual devices created within Olhares (Im)possíveis enable young people to build new forms of relationship with the city and with themselves? The methodological path is cartographic and essayistic, inspired by research modes that are built through encounters and drift. The investigation is carried out with the group, not only about it, accompanying its creative processes, pauses, and re-beginnings. The procedures include analysis of films and photographs, listening to and transcribing recorded conversations, revisiting personal and collective archives, and writing as a practice of montage. The work assumes an experimental tone, becoming a gesture of montage that reveals the power of audiovisual creation to generate shared narratives, affections, and futures.
Visual traces for (im)possible experiences: pedagogies for seeing and narrating the city
Keywords: experiência; montagem; imagem; cidade; educação; experience; montage; image; city; education; CIENCIAS HUMANAS::EDUCACAO; 4. Educação de Qualidade